Qualitative Phenomenological Study: Understanding the Experience of Adolescents’ Mental Health Problems in Urban Areas - Riris Diana Rachmayanti; Andrei Ramani; Nur Farida Kusumawati; Yulia Wardita; Ayu Citra Mayasari; Anysiah Elly Yulianti; Dani Nasirul Haqi (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Adolescence is referred to as a period of "storm and pressure" or "storm & stress". At that time, emotional tension increased as a result of physical, glandular, and hormonal changes. This condition causes them to experience stress to mental health problems. Adolescents who experience mental health problems will have a serious impact on adulthood. This study aims to explore mental health problems (stress) experiences from the perspective of adolescents.Method: The method used in this research was qualitative, with a phenomenological approach, and the participants were adolescents aged 15-18 years. The research employed purposive sampling, with 12 participants. Data collection was conducted through semi-structured interviews, with each interview lasting 30-60minutes. Thematic was used for data analysis.Result : The result shows that the experience of mental health problems related to stress begins in elementary school, junior high school, and senior high school. Stress is the most common among adolescents, categorized as low, moderate, and high. It is based on the PSS (Perceived Stress Scale) instrument. Determinants include family factors, individual factors, academic factors, relationship factors, and the social environment in which adolescents live. Coping mechanisms include both positive and negative responses to stress.